The prevalence of gastroesophageal reflux disease among hospital employees. Issue 5 (1st July 2014) - Ercelep, O. B.; Caglar, E.; Dobrucali, A.
Summary: Quantitative estimate of the actual prevalence of the gastroesophageal reflux disease (GERD ) is difficult to obtain because most of the patients with heartburn have intermittent symptoms. The aim of this study was to assess the frequency of typical and atypical symptoms suggesting GERD to investigate the association of habits and social conditions reported to lead to reflux in the employees of hospital. A total of 2037 collected forms were assessed. The prevalence of GERD was found to be 21.7% (442). The prevalence of symptoms other than heartburn in employees with and without GERD symptoms were 6.6% versus 3.4% (P < 0.05) for asthma, 27.6% versus 8.3% (P < 0.001) for night cough, 50% versus 19.5% (P < 0.001) for noncardiac chest pain. Dyspeptic complaints were found to be significantly higher among GERD patients (P < 0.001). By multiple logistic regression analysis, female gender (odds ratio [OR ] 1.30, 95% confidence interval [CI ] 1.03–1.60, P = 0.027), non-steroidal anti-inflammatory drug medication (OR 1.29, 95% CI 1.03–1.60, P = 0.021) and body mass index over 30 (OR 2.26, 95% CI 1.60–3.18, P < 0.001) were independent risk factors associated with GERD symptoms. GERD is a common health problem in T urkey, and its prevalence is similar to that of W estern populations with different symptom profiles. Female gender, non-steroidal anti-inflammatory drug, and body mass index >30 kg/m 2 were independent risk factors associated with GERD symptoms. Age, alcohol, coffee, tea, and tobacco smoking do not seem to be risk factors for reflux.